2022
DOI: 10.1111/febs.16638
|View full text |Cite
|
Sign up to set email alerts
|

Upstream lipid and metabolic systems are potential causes of Alzheimer's disease, Parkinson's disease and dementias

Abstract: Brain health requires circuits, cells and molecular pathways to adapt when challenged and to promptly reset once the challenge has resolved. Neurodegeneration occurs when adaptability becomes confined, causing challenges to overwhelm neural circuitry. Studies of rare and common neurodegenerative diseases suggest that the accumulation of lipids can compromise circuit adaptability. Using microglia as an example, we review data that suggest increased lipid concentrations cause dysfunctional inflammatory responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 155 publications
(181 reference statements)
1
5
0
Order By: Relevance
“…In the present study, ORF3a expression in the brain disrupted the autophagy–lysosomal pathway as evidenced by increased levels of LC3B and p62 in AAV‐ORF3a–injected mice, suggesting impaired autophagosome‐lysosome fusion. In line with a block in the autophagy–lysosomal pathway, we found that ORF3a‐expressing brain contained abnormal accumulations of gangliosides GM3 and GM2, 2 intermediates in the degradation pathway of gangliosides that are often present at elevated levels in lysosomal storage diseases and other neurodegenerative disorders 24,26,49–51 . We also observed that expression of α‐synuclein, whose levels are maintained by autophagy and lysosomal degradation, 40 was increased in neurons in ORF3a‐expressing brain.…”
Section: Discussionsupporting
confidence: 67%
“…In the present study, ORF3a expression in the brain disrupted the autophagy–lysosomal pathway as evidenced by increased levels of LC3B and p62 in AAV‐ORF3a–injected mice, suggesting impaired autophagosome‐lysosome fusion. In line with a block in the autophagy–lysosomal pathway, we found that ORF3a‐expressing brain contained abnormal accumulations of gangliosides GM3 and GM2, 2 intermediates in the degradation pathway of gangliosides that are often present at elevated levels in lysosomal storage diseases and other neurodegenerative disorders 24,26,49–51 . We also observed that expression of α‐synuclein, whose levels are maintained by autophagy and lysosomal degradation, 40 was increased in neurons in ORF3a‐expressing brain.…”
Section: Discussionsupporting
confidence: 67%
“…Although alterations in lipid metabolism and the balance of their species, known as lipid homeostasis (herein referred to as lipidostasis , in analogy to proteostasis), is deeply associated with neurodegeneration in PD (also reviewed in [ 5 , 33 , 39 , 55 , 59 , 107 ]), the molecular mechanisms involved are still poorly understood. Nevertheless, integrated genome-wide association studies (GWAS) of PD show that several of the possible pathways implicated in PD are directly or indirectly connected with lipidostasis [ 103 ].…”
Section: Introductionmentioning
confidence: 99%
“…Knockdown or deficiency of α-synuclein in rodents induces nigral dopaminergic neuron loss degeneration 70 and increased viral load in the brain following viral infection 67 . Such acute inflammatory activations and elevated α-synuclein are likely efficiently handled and resolved by the brain, however, sustained or repeated inflammatory stimuli, combined with environmental and genetic factors, could prevent the resolution of inflammatory and protein responses in the brain 71 , and eventually lead to reduced clearance of α-synuclein, as well as other aggregation-prone proteins associated with neurodegenerative disease pathology 27 , 28 . Patients with post-COVID-19 syndromes exhibit elevated neurofilament-light and phosphorylated Tau levels, and impaired amyloid processing in the CSF, further illustrating an association between viral-inflammatory responses and increases in proteins that are linked with neurodegenerative disease 72 , 73 .…”
Section: Discussionmentioning
confidence: 99%